Use of malted pulses to formulate gluten-free fresh-egg pasta - Cimini, Alessio; Poliziani, Alessandro; Morgante, Lorenzo; Moresi, Mauro (Italian Journal of Food Science, 2024)
In spite of the fact that legumes are rich in proteins, dietary fibers, and micronutrients, their average per capita consumption is limited because of their lengthy cooking period, unpleasant flavor, low-digestible proteins, and gastrointestinal problems. This study was aimed at assessing the effectiveness of the malting process of three typical pulse seeds of the Italian Latium region (i.e. Gradoli Purgatory beans [GPB]; Onano lentils [OL]; and Solco Dritto chickpeas [SDC]) to minimize their anti-nutrient content and test their use as ingredient in the preparation of gluten-free fresh egg pastas. All these fresh egg pastas were devoid of flatulence-inducing oligosaccharides with low phytate content (0.6–0.80 g/100 g of dry matter, dm), a crude protein content of around 20 g/100 g dm and in vitro glycemic index ranging from 28% to 38%. However, the only fresh egg pasta, including malted GPB flour, exhibited not only a significantly smaller glycemic index (28%±3%) but also a resistant starch–total starch ratio by far greater than the threshold value (14%) specified by the European Commission Regulation 432/2012 to label foods with the health claim indicating improvement in postprandial glucose metabolism.